Regulation of visfatin by microbial and biomechanical signals in PDL cells - Nogueira, Andressa Vilas Boas [UNESP]; Nokhbehsaim, Marjan; Eick, Sigrun; Bourauel, Christoph; Jäger, Andreas; Jepsen, Søren; Cirelli, Joni Augusto [UNESP]; Deschner, James (Springer Nature, 2013)
Objectives: This in vitro study was established to examine whether visfatin thought to be a link between periodontitis and obesity is produced by periodontal ligament (PDL) cells and, if so, whether its synthesis is modulated by microbial and/or biomechanical signals. Materials and methods: PDL cells seeded on BioFlex® plates were exposed to the oral pathogen Fusobacterium nucleatum ATCC 25586 and/or subjected to biomechanical strain for up to 3 days. Gene expression of visfatin and toll-like receptors (TLR) 2 and 4 was analyzed by RT-PCR, visfatin protein synthesis by ELISA and immunocytochemistry, and NFκB nuclear translocation by immunofluorescence. Results: F. nucleatum upregulated the visfatin expression in a dose- and time-dependent fashion. Preincubation with neutralizing antibodies against TLR2 and TLR4 caused a significant inhibition of the F. nucleatum-upregulated visfatin expression at 1 day. F. nucleatum stimulated the NFκB nuclear translocation. Biomechanical loading reduced the stimulatory effects of F. nucleatum on visfatin expression at 1 and 3 days and also abrogated the F. nucleatum-induced NFκB nuclear translocation at 60 min. Biomechanical loading inhibited significantly the expression of TLR2 and TLR4 at 3 days. The regulatory effects of F. nucleatum and/or biomechanical loading on visfatin expression were also observed at protein level. Conclusions: PDL cells produce visfatin, and this production is enhanced by F. nucleatum. Biomechanical loading seems to be protective against the effects of F. nucleatum on visfatin expression. Clinical relevance: Visfatin produced by periodontal tissues could play a major role in the pathogenesis of periodontitis and the interactions with obesity and other systemic diseases. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Biomechanics; Forces; Fusobacterium nucleatum; Periodontal ligament; Tension; Visfatin